2019
DOI: 10.1002/zaac.201900067
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach for Synthesis of Low‐moisture Glycidyl Azide Polymer

Abstract: In this work, low‐moisture glycidyl azide polymer (GAP) was successfully prepared using a modified two‐step method. The modified method resembles the structure of the classical two‐step method, which is widely used to prepare the GAP. Firstly, epichlorohydrin (ECH) is polymerized into polyepicholorohydrin (PECH), which is subjected afterward to azidation step using sodium azide (NaN3). Interestingly, minimizing the water content in the final GAP product, which is a challenging when dealing with GAP as a rocket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The results showed that the addition of the variety of prepolymers improved the mechanical brittleness of GAP-based elastomers. Abdelhafiz and Elbeih 14 successfully prepared a low-moisture GAP using a modified two-step method, where epichlorohydrin was polymerized into polyepichlorohydrin and subjected afterward to the azidation step using sodium azide. Besides, it is also reported that the linear GAP can be modified to the branched GAP with a lower viscosity than that of the linear GAP, which was then cross-linked with the curing agent to prepare thermosetting energetic elastomers.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the addition of the variety of prepolymers improved the mechanical brittleness of GAP-based elastomers. Abdelhafiz and Elbeih 14 successfully prepared a low-moisture GAP using a modified two-step method, where epichlorohydrin was polymerized into polyepichlorohydrin and subjected afterward to the azidation step using sodium azide. Besides, it is also reported that the linear GAP can be modified to the branched GAP with a lower viscosity than that of the linear GAP, which was then cross-linked with the curing agent to prepare thermosetting energetic elastomers.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 Low molecular weight triols such as TMP and triethanolamine were used as crosslinkers in different types of research. 29 35 The most significant key parameter for binder system is the CLD which defined as moles of elastically effective matrix chains per unit volume. In addition to CLD, there are other parameters which determine the mechanical and physical properties of the binder such as network configuration, micro inhomogeneity, and polymer chains chemical nature.…”
Section: Introductionmentioning
confidence: 99%